The Effectiveness of the Mulgraning Model With Google Classroom for Enchancing Media And Digital Literacy - Vivi Indriyani; Jasmienti; M. Aries Taufiq; Nofrahadi; Herland Franley Manalu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The rapid development of digital technology has encouraged the integration of media and digital literacy into classroom practice so that students are able to access, analyze, evaluate, manage, and create information critically and responsibly. Responding to this need, this study aimed to examine the effectiveness of the Multiliteracy Integrative Learning (MULGRANING) model assisted by Google Classroom in improving students’ media and digital literacy within scientific text learning. This research employed a descriptive quantitative method involving 68 grade XI students from two public high schools in Padang City as participants. Data were collected using an expert-validated observation sheet that systematically assessed students’ literacy performances during the learning process, covering indicators of information access, evaluation, management, and utilization. The descriptive analysis revealed varied literacy tendencies among students, with 38.24% categorized as high, 44.12% moderate, and 17.64% low. These findings demonstrated that the implementation of the MULGRANING model effectively supported the development of media and digital literacy, particularly in indicators related to accessing, selecting, and critically evaluating digital information. However, the aspects of information management and utilization were still predominantly in the moderate category, suggesting that students require further guidance in organizing information and applying it to solve problems or produce scientific work. Overall, this study provides empirical evidence regarding the potential of technology-assisted learning models to strengthen students' media and digital literacy competencies. These findings highlight the importance of integrating digital platforms to create more innovative and relevant learning environments.